PENGARUH KEGUNAAN YANG DIRASAKAN, SIKAP MEREK DAN PERSEPSI HARGA TERHADAP NIAT MEMBELI KEMBALI MELALUI KEPERCAYAAN ELEKTRONIK DAN KEPUASAN PELANGGAN PENGGUNA TRANSPORTASI ONLINE MAXIM DI DKI JAKARTA - Muhammad Fajriansyah Malik; Hanny Nurlatifah; Shohibul Imam (Jurnal Ekonomi dan Industri, 2024)
This study aims to analyze whether there is an influence between Perceived Usefulness, Brand Attitude, Price Perception on Repurchase Intention through E-Trust and Customer Satisfaction in Maxim online transportation users. The sample in this study amounted to 100 respondents using purposive sampling where there are criteria for determining the sample, namely users of online transportation applications who have used Maxim in DKI Jakarta at least once in the last 3 months. This study uses quantitative methods and path analysis tests. Based on the test results, it is known that Brand Attitude, Price Perception on Repurchase Intention has a direct effect and for indirectly Brand Attitude on Repurchase Intention through Customer Satisfaction.